Information technologies in cardiology: potential for further development - O. M. Drapkina (Российский кардиологический журнал)
Medical education is based on a continuous, life-long desire of doctors to obtain reliable professional information. Distant learning in medicine, the so-called “educational system of the 21st century”, stems from both the need for rapid sharing and accumulation of information and the doctors’ need for continuous selfeducation. Modern distant learning incorporates two key elements: the medium of the information exchange (such as mail, TV, radio, and Internet) and the methods dependent of the information communication type. As a part of the Russian Cardiology Society’s activities, the section “Information Technologies in Cardiology” facilitates generation, accumulation, and dissemination of medical information, using computer-based technologies and communications, such as Internet technologies which provide doctors with an access to professional medical knowledge in the field of cardiology.